The Influence of Innovation, Digital Literacy, and Entrepreneurial Literacy on Business Sustainability (Study on Food MSMEs in Sukabumi City) - Siti Nuraeni; R. Deni Muhammad Danial; Tetty Sufianty Zafar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of innovation, digital literacy, and entrepreneurial literacy on business sustainability in the food MSME sector in Sukabumi City. Business sustainability is an important issue in facing market dynamics and competitive challenges, especially for small and medium business actors. The method used in this study is a quantitative method, which produces findings through statistical and measurement procedures. The approach applied is descriptive and associative, with a survey research type. The sample of this study consisted of 100 food MSME actors in Sukabumi City who were selected using probability sampling techniques, namely simple random sampling. Data were collected through questionnaires and the data analysis techniques used in this study were classical assumption tests, multiple correlation coefficients, determination coefficients, multiple linear regressions, and simultaneous (F test) and partial (T test) hypothesis tests. The results of the study indicate that innovation, digital literacy, and entrepreneurial literacy have a positive and significant effect on business sustainability, this can be seen from the calculated t value> t table, where the innovation variable has a calculated t value of 2.908> t table 1.661 and a significance value of 0.005 <0.05. Digital literacy has a calculated t value of 3.146> t table 1.661 and a significance value of 0.002 <0.05. And entrepreneurial literacy has a calculated t value of 5.255> t table 1.661 and a significance value of 0.000 <0.05.